Simple realization of 5-Segment discontinuous SVPWM based on FPGA - Sutikno, Tole; Jidin, Auzani; Basar, Mohd Farriz (International Association of Computer Science and Information Technology Press (IACSIT), 2010)
The Space Vector Pulse Width Modulation (SVPWM) is possibly the best among all the PWM techniques for variable frequency drive applications. Unfortunately, the modulation algorithm is mainly implemented with software based on microcontroller or digital signal processors (DSP). These are software-based technique purely and obviously not an ideal solution. Employing Field Programmable Gate Array (FPGA) to realize SVPWM strategies provides advantages that it is considered as an appropriate solution to boost system performance of an SVPWM algorithm. Moreover, although in the literatures the implementation for three-phase SVPWM based on FPGA is not lacking, however all these designs are based on the conventional SVPWM without considering hardware-resource saving and not simple. This paper present a simple realization of 5-segment discontinuous SVPWM with a difference approach based on FPGA, in which the judging of sectors and the calculation of the firing time to generate the SVPWM waveform is simple, and also the switching losses is low. The proposed discontinuous SVPWM has been designed and successfully implemented by using APEX20KE Altera FPGA considering hardware-resource saving and has successfully driven a three phase inverter system with induction machine 1.5 kW as load.